Experience in management of emergency and severe cases of non-COVID-19 during the outbreak of COVID-19 - Yu, Weimin (Am J Infect Control, 2021)
In China, the COVID-19 epidemic has had a definite turning point under the nationwide efforts to combat it. The battle against the epidemic has lasted for more than one and a half months and will continue in the short term. Severe infectious risks, massive consumption of medical personnel and materials bring unprecedented challenges to the treatment of non-COVID-19 with emergency and severe cases. To improve the management of emergency and severe cases of non-COVID-19 during the epidemic period, attention should be paid not only to "cure" but also to "prevent." Through the prehospital triage and in-hospital buffer, this paper provides the admission and treatment experience for emergency and severe cases of non-COVID-19, expecting to provide a valuable reference for saving more patients during the outbreak of COVID-19.